Integrating Stability Assessments Under the Financial Sector Assessment Program into Article IV Surveillance. (Policy Papers; Policy Paper ;, 2010)
Integration of financial sector issues into bilateral surveillance has been a long-standing challenge. Financial stability is a key component of the domestic and external stability of members and is important for the promotion of the 'stable system of exchange rates' envisaged under Article IV. But although financial sector issues and policies are at the core of the Fund's surveillance mandate, their effective integration has been a challenge. To address this challenge, it is proposed to adopt a more risk-based approach to financial sector surveillance by making FSAP stability assessments part of Article IV surveillance for members with systemically important financial sectors.